Strategic Dimensions of Islamic Banking: A Focus on Service Quality and Facilities Impacting Savings - Budiarti, Sari; Roisiyatin, Roisiyatin; Aziz, Abdul; Masriah, Siti; hopipah, Popi (Li Falah: Journal of Islamic Economics and Business, 2023)
This study aims to examine the effect of administrative service quality and office facilities on savings premiums at Indonesian Islamic banks (BSI). The position of research from existing research is by setting 3 (three) hypotheses, including H1: Service Quality (X1) has a positive effect on Interest in Saving (Y). H2: Facility Quality (X2) has a positive effect on Interest in Saving (Y). H3: Service Quality (X1) and Facility Quality (X2) together have a positive effect on Interest in Saving (Y). The data in this study were obtained through a questionnaire consisting of three variables using a Likert scale on customers or users of Bank Syariah Indonesia (BSI). The data testing method in this study is to use SPSS version 25, namely by testing the validity test, reliability test, simple linear regression analysis, R2 determinant coefficient test (simulation test) and partial test (t-test). The findings of the results of this study are that the quality of service and facilities have a positive and significant effect on saving intentions. This result shows that quality facilities and services strongly influence customer interest in saving. In addition, this aspect contributes to the company's profits. Customer satisfaction will increase in proportion to the level of service quality of the company, which in turn will have a positive effect on the Interest in saving Bank Syariah Indonesia. The findings of this study are expected to provide new knowledge, especially in management science.